Intrinsic Motivation on Entrepreneurs' Intention to Adopt Crowdfunding: The Case of Kiva Lending Crowdfunding - Ndumbaro, Felista; Mofulu, George Mofulu; Ndaki, Daudi Pascal (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
The study investigated the entrepreneur's intrinsic motivation and its relationship to the adoption of crowdfunding using a Kiva lending crowdfunding platform as case study. A total 241 entrepreneurs in Tanzania were surveyed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM 3) to examine whether perceived behavioural control, personal attitude, and self-efficacy were predictors of entrepreneurs’ intention to adopt crowdfunding. The results indicated that an entrepreneur's self-efficacy, attitude, and perceived behaviour control significantly determine their intention to adopt crowdfunding. The study revealed that entrepreneurs who engaged in crowdfunding possessed a high degree of self-assurance in their abilities, indicating that they were confident in their capacity to perform the necessary tasks to complete the fundraising process. Moreover, the research highlights the importance of understanding the attitudes of entrepreneurs towards crowdfunding. Entrepreneurs with positive attitudes towards crowdfunding were more likely to engage in it to raise funds for their venture. The findings suggested that crowdfunding platforms should pay attention to the attitudes of entrepreneurs towards crowdfunding to understand their motivations and expectations better. This will enable crowdfunding platforms to tailor their services to meet the needs and expectations of entrepreneurs, ultimately resulting in a more successful crowdfunding experience for all parties involved.